2022
DOI: 10.1167/tvst.11.1.30
|View full text |Cite
|
Sign up to set email alerts
|

Effects of Valproic Acid and Mitomycin C Combination Therapy in a Rabbit Model of Minimally Invasive Glaucoma Surgery

Abstract: Purpose This study aimed to compare the effectiveness of combination therapy consisting of low-dose mitomycin C (MMC) and valproic acid (VPA) against high-dose MMC for improving the scar phenotype in minimally invasive glaucoma surgery (MIGS). Methods A rabbit model of MIGS incorporating the PreserFlo MicroShunt was treated with high (0.4 mg/mL) or low (0.1 mg/mL) doses of MMC or with combination therapy consisting of low-dose (0.1 mg/mL) MMC and VPA. Operated eyes were… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(3 citation statements)
references
References 49 publications
0
3
0
Order By: Relevance
“…Additionally, VPA was found to suppress collagen and fibronectin gene expression, while enhancing the expression of factors disrupting TGF-β pathways. Another study comparing the concomitant usage of VPA and MMC with varying doses of MMC in a rabbit model of the PreserFlo ® MicroShunt found that the combination therapy was less cytotoxic when compared to MMC alone [70]. Moreover, the combination decreased VEGF and collagen gene expression more than MMC alone was able to.…”
Section: Wound Healing After Glaucoma Drainage Devices (Gdds) and Ble...mentioning
confidence: 99%
“…Additionally, VPA was found to suppress collagen and fibronectin gene expression, while enhancing the expression of factors disrupting TGF-β pathways. Another study comparing the concomitant usage of VPA and MMC with varying doses of MMC in a rabbit model of the PreserFlo ® MicroShunt found that the combination therapy was less cytotoxic when compared to MMC alone [70]. Moreover, the combination decreased VEGF and collagen gene expression more than MMC alone was able to.…”
Section: Wound Healing After Glaucoma Drainage Devices (Gdds) and Ble...mentioning
confidence: 99%
“…This progression is due to the MMC-induced apoptosis of conjunctival connective fibroblasts [ 120 ]. The toxic effects of MMC may be mitigated by combining a lower dosage of MMC with valproic acid, which has been demonstrated in a rabbit model [ 121 , 122 ]. There is no definite clinical recommendation for post-operative 5-FU as opposed to MMC.…”
Section: Strategies To Prevent Ocular Fibrosis Following Glaucoma Fil...mentioning
confidence: 99%
“…Although MMC reduces scar formation, bleb failure is a common outcome despite its use [ 5 ]. Using MMC also carries the risk of significant side effects, including conjunctival epithelium breakdown, hypotony, and endophthalmitis [ [6] , [7] , [8] , [9] ]. Consequently, effective and safe adjuncts to glaucoma filtering surgery that prevent the excessive deposition of collagen-rich scar tissue would potentially reduce or inhibit channel blockage, thus reducing the need for repeat surgeries.…”
Section: Introductionmentioning
confidence: 99%